2003
DOI: 10.1116/1.1579697
|View full text |Cite
|
Sign up to set email alerts
|

Gas-induced current decay of molybdenum field emitter arrays

Abstract: Articles you may be interested inDevelopment of a cold-cathode electron gun for cathode-ray tube using a Mo-tip field-emitter array Effect of O 2 on the electron emission characteristics of active molybdenum field emission cathode arrays Field emission displays can be seriously limited by current degradation of Mo field emitter arrays, primarily due to inadequate vacuum conditions inside their thin vacuum packages. Most lifetime studies describe the deleterious effects of short exposures to oxygenic gases on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…3,16 As one underlying mechanism of the emission homogeneity improvement, we consider that bombardment of emitters by noble-gas ions, that were generated by electron impact ionization near current-emitting tips, caused sputtering 6 or ion-implantation. 17 From the expected R tip -dependences for A FN ($NR tip 2 ) and B FN ($(R tip ) 0.5 ) with the FN exponent n of 2, the observed increase of A FN and B FN was compatible with the increase of R tip by sputtering-induced tip-blunting and removal of adsorbate and native oxide. Preferential sputtering of oxygen atoms from partially oxidized molybdenum emitter surface could also contribute to this.…”
Section: Indexmentioning
confidence: 77%
“…3,16 As one underlying mechanism of the emission homogeneity improvement, we consider that bombardment of emitters by noble-gas ions, that were generated by electron impact ionization near current-emitting tips, caused sputtering 6 or ion-implantation. 17 From the expected R tip -dependences for A FN ($NR tip 2 ) and B FN ($(R tip ) 0.5 ) with the FN exponent n of 2, the observed increase of A FN and B FN was compatible with the increase of R tip by sputtering-induced tip-blunting and removal of adsorbate and native oxide. Preferential sputtering of oxygen atoms from partially oxidized molybdenum emitter surface could also contribute to this.…”
Section: Indexmentioning
confidence: 77%
“…The substrate-to-anode distance was kept to 100 μm. Several conditioning runs were always conducted before the final stable and reproducible curves were recorded. , Each I – U curve is the average of at least three current–voltage scans, and each current value in a scan is the average of 10 measurements at that voltage.…”
Section: Methodsmentioning
confidence: 99%
“…2 However, more research has to be performed searching for emitter materials that are capable of high currents, are environmentally tolerant, and have stable emission. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The purpose of this article is to assess the field emission properties of the HfC coated Si FEAs ͑hereinafter called HfC FEAs͒ as compared to ͑noncoated͒ Si FEAs, when subject to residual gases. [3][4][5][6][7][8][9][10] Several studies related to the emitter operation in gas ambient have been reported, concerning especially Spindt-type emitters.…”
Section: Introductionmentioning
confidence: 99%